(untitled) (UNIZIK Journal of Marketing, 2026)
This study investigates the relationship between online customer experience and customer loyalty among undergraduates who are users of bank apps in Bayelsa State, Nigeria. Anchored in Information Systems (IS) continuance theory, the study conceptualizes OCX as a multidimensional construct comprising functional experience, information experience, and aesthetic experience. A correlational, cross-sectional survey design was adopted, and data were collected from undergraduate students of a public university in Bayelsa State using an online questionnaire. From a sample of 377 respondents, 239 valid responses were analyzed using exploratory factor analysis, reliability testing, and correlation analysis. Exploratory factor analysis revealed a three-factor structure of online customer experience, differing from the initially hypothesized dimensions. Correlation analysis results indicate that functional experience, information experience, and aesthetic experience all have significant relationships with customer loyalty. Among these, information experience was found to have the strongest relationship with customer loyalty. The findings highlight the importance of app usability, quality and reliability of information, and interface aesthetics in fostering both attitudinal and behavioral loyalty.